Molecular phylogeny of Niphargus boskovici (Crustacea: Amphipoda) reveals a new species from epikarst - Švara, Vid; Delić, Teo; Rađa, Tonći; Fišer, Cene (Zootaxa, 2015)
We describe a new species of an amphipod Niphargus zagorae sp. n. and redescribe its nearest relative and morphologically similar species N. boskovici S. Karaman, 1952. We present the geographic distributions of both species, morphological diagnoses and infer their phylogenetic position within the genus based on COI, 28S and H3 markers.